Is isometrics effective on pain perception, functional mobility and anxiety of geriatric clients with osteoarthritis at Pathanamthitta District, Kerala - Nisha, M.D. (Journal of Biomedical Sciences, 2019)
Background: Osteoarthritis is a major cause of many medical conditions and disability in people above 50’s and leads to reduced activity in older people. Global statistics revels that over 100 million people worldwide suffers from Osteoarthritis. Materials and methods: A quasi experimental pretest - posttest control group design was used. 200 geriatric clients with osteoarthritis residing in selected geriatric homes at Pathanamthitta were selected and assessed by using a Numerical Pain Intensity Scale, an Observational check list and a three point rating scale for pain, functional mobility and anxiety. Results: There was a significant difference between the mean pain score( t = 10.758 p = 0.01, df – 198), functional mobility ( t = 7.73 p = 0.01, df – 198) and anxiety (t = 7.665 ,df –198, p=0.01in experimental and control group after intervention ( t = 10.758 p = 0.01, df – 198).Statistically no significant association was found between pain, functional mobility and anxiety with variables such as gender, religion, marital status, number of children’s and duration of stay.The pain and anxiety correlation value was ‘r’ = 0.89. The functional mobility and anxiety correlation value was ‘r’ = 0.80. The functional mobility and pain correlation value was ‘r’ = 0.83. It shows that statistically positive correlation is present between the geriatric clients’ pain and anxiety, functional mobility and anxiety and functional mobility and pain at p<0.05% level of significance. Conclusion: Exercise is one of the best methods to treat Osteoarthritis. This study proved that isometric exercises are beneficial to improve the functional mobility of joints in old age people. When the mobility increases, intensity of joint pain decreases.